The Evolution of the Text Encoding Initiative: From Research Project to Research Infrastructure - Lou Burnard (OpenEdition, 2013)
It is twenty-five years since the Text Encoding Initiative was first launched as a research project following an international conference funded by the US National Endowment for the Humanities. This article describes some key stages in its subsequent evolution from research project into research infrastructure. The TEI's changing nature, we suggest, is partly a consequence of its close and highly responsive relation with an active user community, which may also explain both its longevity and its effectiveness as a part of the digital humanities research infrastructure.